2020
DOI: 10.22207/jpam.14.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Hepatitis A and Hepatitis E Viruses among the Acute Viral Hepatitis Cases in Tertiary Care Hospital –A Four Years Retrospective Study

Abstract: Acute viral hepatitis(AVH) is caused by Hepatitis A (HAV) and Hepatitis E(HEV). It is major health burden in India. Both the viruses HAV and HEV are primarily transmitted via the faeco-oral course. Study was conducted to determine the seroprevalence of HAV, HEV and rate of co-infection in AVH patients attending rural tertiary care centre. A retrospective laboratory record based study was carried out in rural tertiary health care center located in Western Maharashtra. Laboratory and Medical records of suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contrast to HEV, HAV exposure is widespread in children. Jaundice, fever, fatigue, and hepatomegaly are common clinical presentations in HAV, HEV, and confection with both viruses in acute viral hepatitis [ 45 ]. The double infection can lead to serious complications and increased mortality due to the high risk of acute liver failure in both children and adults.…”
Section: Hav Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to HEV, HAV exposure is widespread in children. Jaundice, fever, fatigue, and hepatomegaly are common clinical presentations in HAV, HEV, and confection with both viruses in acute viral hepatitis [ 45 ]. The double infection can lead to serious complications and increased mortality due to the high risk of acute liver failure in both children and adults.…”
Section: Hav Ratementioning
confidence: 99%
“…Another study conducted in Bangladesh reported that the double infection rate is about 5.3% [ 47 ]. The coinfection rate has decreased in recent years, from 2006–2020, and this may be the result of a high rate of HAV vaccination and improved sanitation [ 45 ]. Furthermore, Marciano et al have discovered an unexpectedly high proportion of coinfection of HAV with both HIV and syphilis.…”
Section: Hav Ratementioning
confidence: 99%